The long-term impact of the 1995 Hanshin-Awaji Earthquake on wage distribution - Fumio Ohtake; Naoko Okuyama; Masaru Sasaki; Kengo Yasui (Osaka University, Institute of Social and Economic Research (ISER), 2014)
This paper explores the effects of the 1995 Hanshin-Awaji Earthquake on the wages of people in the area of the earthquake over the 17 years after its occurrence and identified which part of the wage distribution has been most affected by this event by comparing the wage distributions of disaster victims and non-victims. To do this, we used three decomposition methods, developed by (i) Oaxaca (1973) and Blinder (1973); (ii) DiNardo, Fortin, and Lemieux (1996) ("DFL"); and (iii) Machado and Mata (2005) and Melly (2006). Our findings are as follows. First, the Oaxaca and Blinder decomposition analysis shows that the negative impact of the earthquake still affects the mean wages of male workers. Second, the DFL decomposition analysis shows that middle-wage males would have earned more had the 1995 Hanshin-Awaji Earthquake not occurred. Finally, the Machado-Mata-Melly decomposition analysis shows that the earthquake had a large, adverse impact on the wages of middle-wage males, and that their wages have been reduced since the earthquake, by 5.0 - 8.6%. This result is similar to that from the DFL decomposition analysis. In the case of female workers, a long-term negative impact of the earthquake was also observed as the wages of high-wage females were reduced by 8.3 - 13.8%.
Keywords: J31; Q54; 330; Natural disasters; Wage distribution; Wage decomposition; Earthquake